2022
DOI: 10.3390/en15207620
|View full text |Cite
|
Sign up to set email alerts
|

Renovation Results of Finnish Single-Family Renovation Subsidies: Oil Boiler Replacement with Heat Pumps

Abstract: Finland has approximately 150,000 oil-heated private homes. In 2020, the Finnish government launched subsidies for private homeowner energy renovations. In this study, we examine the impact of two new energy renovation subsidies, the ELY grant and the ARA grant, from an energy efficiency point of view. Data from these subsidies reveal that a typical energy renovation case is a building from the 1970s where the oil boiler is replaced with an air-to-water heat pump. With additional data from the Finnish Energy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Therefore, ASHP can provide both heating and cooling under climate variations. Sankelo et al (2022) further confirmed that ASHP is the favourite option (66%) for replacing oil boilers in Finland. The energy demand of ASHP can further be reduced by incorporating additional heat insulation.…”
Section: Renewable Measuressupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, ASHP can provide both heating and cooling under climate variations. Sankelo et al (2022) further confirmed that ASHP is the favourite option (66%) for replacing oil boilers in Finland. The energy demand of ASHP can further be reduced by incorporating additional heat insulation.…”
Section: Renewable Measuressupporting
confidence: 53%
“…GSHP can provide thermal comfort with a comparatively lower amount of energy consumption in both cold and temperate regions (Akgüç and Yılmaz, 2022; Sankelo et al , 2022) by taking advantage of the earth’s relatively constant temperature through all seasons. GSHP can extract heat from the earth and vice versa.…”
Section: Climate-resilience Of Retrofit Measuresmentioning
confidence: 99%
“…These generally found that GSHPs had lower environmental impacts than conventional and ASHP systems. The GSHP was more energy-efficient than a conventional system N/A Favourable x x x x [113,114] The GSHP had lower energy consumption compared to conventional system N/A Favourable x [115] The GSHP had lower energy consumption compared to the conventional system N/A Favourable x [116] The GSHP saved energy consumption in heating mode compared to the conventional system N/A Favourable x x [117] The GSHP had lower energy consumption than the conventional system N/A Favourable x [38] The GSHP had lower energy consumption compared to ASHP N/A Favourable x x x x [75] The GSHP was more energy-efficient than the ASHP N/A Favourable x x x [110] The GSHP was more energy-efficient than conventional system N/A Favourable x [85] The GSHP was more energy-efficient than the ASHP N/A Favourable x [118] The GSHP was more energy-efficient than the conventional systems NA Favourable x x x [119] The GSHP showed higher efficiency for cooling than heating…”
Section: Ashps For Caged and Free-run Poultry Housing Applicationsmentioning
confidence: 99%
“…The GSHP met the cooling load requirements N/A Favourable x [89] The GSHPs used less operational energy than the conventional and ASHP systems N/A Favourable x x x [114] The GSHPs used less energy than the conventional systems…”
Section: Ashps For Caged and Free-run Poultry Housing Applicationsmentioning
confidence: 99%
“…The authors of [10] carried out a comparative analysis of the economic costs of converting the heating system of private houses from oil boiler units to thermal refrigeration units. The authors of [11] conducted a numerical experiment and formulated recommendations for the selection of heat pumps in relation to various production processes.…”
Section: Introductionmentioning
confidence: 99%